Characterization and assessment of saltwater intrusion into the coastal aquifers of Guimaras Island, Philippines - Hernandez, Bryan Clark B. (College of Engineering, University of the Philippines Diliman, 2014)
Groundwater resources, with its ease of use, natural storage and accessibility, are vulnerable to exploitation because the demand for ground water increases for human consumption, such as agricultural, industrial and domestic usage. If not properly mitigated, excessive withdrawals could affect the health of the aquifer systems and induce creeping contamination into these resources, like saltwater intrusion. In island ecosystems like Guimaras, with its oceanic setting, gentle slopes, seasonal rainfall pattern and relatively shallow water tables, addressing the issues and threats of saltwater intrusion should be in place through comprehensive groundwater monitoring and assessment to identify appropriate management and mitigation techniques. However, hydrogeological data of the groundwater network are limited, thus hindering efforts to conduct research, planning and management options. To cope with data-poor conditions, available secondary data were validated and preliminary surveys were done to create baseline or reference database. Thirty-one wells around the island were characterized for salinity, total dissolved solids and groundwater level changes. Five critical areas (coastal baranggays) were identified as critical using spatio-temporal analysis of the parameters. Since groundwater dynamics are complex, conventional techniques should be upgraded to include state-of-the-science instrumentation for better accuracy and analysis. Continuous monitoring devices that would detect changes in groundwater levels and salinity were installed in the five coastal wells selected. These wells are located 50 800 meters away from the coast. Geophysical and geochemical techniques were conducted to investigate saltwater intrusion dynamics under seasonal variations. Electrical resistivity tomography (ERT) surveys were done to reveal saltwater encroachment into the study wells. Groundwater samples were analyzed for chloride content by lon Chromatography method. Saltwater intrusion can be caused by natural and anthropogenic drivers. The island's vulnerability to sea level rise was assessed using the GALDIT index method. The water and land use patterns that may enhance saltwater intrusion were also considered. Strategies to address the issue of saltwater intrusion were also recommended through effective groundwater information management, groundwater balance assessment and simulations and policy framework on water and land uses affecting the hydrologic processes of the island. In summary, this research was able to contribute to the understanding of saltwater intrusion patterns and was able to provide a template to other island ecosystems with similar experience, and establish a better reference for groundwater management and planning for the local government.